"Dear Mr. Blackwell, How He Has Helped!": Toward an Anatomy of Ally Rhetoric. Issue 3 (1st September 2020) - Hanly, J. P.
ABSTRACT: This article draws on archival research to examine the career of one of the nineteenth-century's most prominent advocates of woman's rights, Henry B. Blackwell. Responding to recent calls by feminist historians of rhetoric for studies reexamining collaboration, coalition, and alliance, I engage with and draw on what a wide range of rhetorical scholars and feminist theorists have suggested about how individuals use language to form alliances and foster change to consider why Blackwell's earliest efforts to speak as an ally were counterproductive and why his later efforts—speaking alongside his wife, Lucy Stone; writing editorials for The Woman's Journal, and speaking after Stone's death—might be seen as gesturing toward an anatomy of ally rhetoric.